ORGANIZATION OF PSYCHOLOGY AND PEDAGOGICAL CARE IN CHILDREN WITH SEVERE CHRONIC HEREDITARY METABOLIC DISEASES REHABILITATION (AT THE MODEL OF MUCOPOLYSACCHARIDOSIS) - S. B. Lazurenko; L. S. Namazova-Baranova (Union of pediatricians of Russia, 2012)
The article contains the issue of correction-pedagogical influence, depending on severity and duration of the disease, structure of the health disorders, grade of the cognitive impairment, type of the emotional reactions and behavioral characteristics of the child, that means independence on the child's age. The stages of corrective and pedagogical care, ways of work with family, organization of the education and training process for children with hereditary metabolic diseases (at the model of mucopolysaccharidosis) are described. It is proved, that including of the corrective and pedagogical care into the rehabilitation provides the observation by the specialists the psychic development dynamics as one of the most significant indicators of children health, increases efficacy of enormous financial costs by means of children socialization and psychological potential of the able-bodied family members preserving.